Development of high-performance electrochromic supercapacitors using copper-based metal-organic framework/reduced graphene oxide composites - Mohanadas, Dharshini (2021)
Supercapacitors (SCs) are promising energy storage devices with tremendous specific capacitance, fast rate for charging/discharging, high specific power and long-life cycle. It is difficult to estimate the state-of-charge of the existing supercapacitors, which leads to excessive charging/discharging. Hence, supercapacitors with more functions and novel features are fabricated to widen the energy storage applications. The electrochromic (EC) materials are able to exhibit visual color changes upon an applied potential. Therefore, it is highly attractive to combine SC and EC characteristics into one device for bifunctional applications namely electrochromic supercapacitor (EC-SC). The EC-SCs can function as a normal supercapacitor to store energy, at the same time, the energy level of the devices can be sensed by observing the changes in visual colors. In this work, copper-based metal-organic framework/reduced graphene oxide (HKUST-1/rGO) composites were successfully developed as high-performance EC-SC devices via hydrothermal and electrochemical deposition. The asfabricated composites were characterized via X-ray diffraction (XRD), Fourier transform infrared spectrometry (FTIR), Raman spectroscopy, field emission scanning microscopy (FESEM) and electrochemical impedance spectroscopy (EIS). Initially, poly(3,4-ethylenedioxythiophene)-reduced graphene oxide/copper-based metal-organic framework (PEDOT-rGO/HKUST-1) was prepared and electrochromic performance was evaluated. PEDOTrGO/ HKUST-1 exhibited a high coloration efficiency of 176.8 cm2/C with high optical contrast. An electrochromic coloration and bleaching times of 1.1 s and 1.3 s were recorded at 500 nm which proved excellent switching kinetics of PEDOT-rGO/HKUST-1. The similar composite also depicted promising supercapacitive properties with remarkable specific energy and specific capacitance of 21.0 Wh/kg and 360.5 F/g, respectively. The HKUST-1/rGO composite was designed as a negative electrode of an asymmetrical supercapacitor (ASC) device. A vanadium oxide/reduced graphene oxide//copper-based metal-organic framework/reduced graphene oxide (V2O5/rGO//HKUST-1/rGO) ASC device successfully delivered enormous specific energy (31.2 Wh/kg) at a specific power of 656.4 W/kg. Nickel oxide/vanadium oxide/reduced graphene oxide//HKUST-1/rGO (NiO/V2O5/rGO//HKUST-1/rGO) and manganese oxide/ vanadium oxide/reduced graphene oxide//HKUST-1/rGO (MnO2/V2O5/rGO//HKUST- 1/rGO) devices were developed for bifunctional asymmetrical electrochromic supercapacitor (EC-SC) devices. The designed PEDOT-rGO/HKUST-1, V2O5/rGO//HKUST-1/rGO, NiO/V2O5/rGO//HKUST-1/rGO and MnO2/V2O5/rGO//HKUST-1/rGO depicted outstanding specific capacitance of 360.5, 483.9, 500 and 652.7 F/g, respectively. Both bifunctional asymmetric ECSC devices (NiO/V2O5/rGO//HKUST-1/rGO and MnO2/V2O5/rGO//HKUST- 1/rGO) were also demonstrated green and orange color at the discharged and charged state, respectively. These results proved that the successfully prepared asymmetrical EC-SC devices with both excellent charge storage capability and outstanding electrochromic properties are promising candidates for bifunctional application.